2012
DOI: 10.1111/j.1365-2958.2011.07953.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the role ofBacillus subtilisσMin β‐lactam resistance reveals an essential role for c‐di‐AMP in peptidoglycan homeostasis

Abstract: Summary The Bacillus subtilis extracytoplasmic function (ECF) σ factor σM is inducible by, and confers resistance to, several cell envelope acting antibiotics. Here, we demonstrate that σM is responsible for intrinsic β-lactam resistance, with σX playing a secondary role. Activation of σM upregulates several cell wall biosynthetic enzymes including one, PBP1, shown here to be a target for the beta-lactam cefuroxime. However, σM still plays a major role in cefuroxime resistance even in cells lacking PBP1. To be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
282
1
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(308 citation statements)
references
References 92 publications
(150 reference statements)
13
282
1
12
Order By: Relevance
“…Furthermore, PG hydrolysis has been implicated in the mechanism of action of many antibiotics that target the cell wall (Rogers et al ., 1983; Tomasz et al ., 1970; Goodell et al ., 1976; Luo and Helmann, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PG hydrolysis has been implicated in the mechanism of action of many antibiotics that target the cell wall (Rogers et al ., 1983; Tomasz et al ., 1970; Goodell et al ., 1976; Luo and Helmann, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…High levels of cyclic-di-AMP have been linked to increased transcript levels of pbp4, a penicillin binding protein, which could explain the increase in peptidoglycan crosslinking (39). In B. subtilis, cyclic-di-AMP plays a role in peptidoglycan homeostasis and its depletion promotes cell lysis (40), suggesting that regulation of wall integrity may be a broadly conserved role for cyclic-di-AMP. Together with the findings of our investigation, this prior work suggests a model in which cyclic-di-AMP levels drop under biofilm-inducing conditions, impairing cell wall integrity and triggering cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the c-di-AMP-specific phosphodiesterase GdpP (previously referred to as YybT (15)) degrades cyclic di-AMP (16). Recently, c-di-AMP was implicated in the control of cell wall homeostasis in B. subtilis, and it was demonstrated that this signaling nucleotide is essential for the growth of the bacterium (15).…”
mentioning
confidence: 99%